The good liar - Mina, Denise (Mulholland Books, 2025)
"A year ago, a father and his fiancée were brutally murdered in their opulent London townhouse, sparking the most high-profile murder investigation in recent history. Blood spatter expert Doctor Claudia O'Sheil's evidence put the killer behind bars--or so everyone believes. But since the trial, Claudia's learned a horrific truth: her evidence and her testimony were wrong. And someone she knows made sure of it. Now, as she takes the stage to give a career-defining speech before London's elite, Claudia faces a devastating choice. Protect her children and her career with her continued complicity, or blow the whole conspiracy apart and reveal the truth: not only is the real murderer still out there, but they're in the audience. As Claudia steps toward the microphone, she revisits that fateful night. What really happened? And what will Claudia say?"--